The Fertility Impact of Changes in the Timing of Childbearing in Nepal - Aryal, T. R. (Nepal Journal of Science and Technology, 2007)
The main aim of this paper is to study the tempo effect in fertility (B-F0 procedure and parity progression-based techniques have been used to check the tempo effects in fertility schedules. B-F procedure has been modified by smoothing annual change in mean age at childbearing over time. Data are taken from NFHS 1996. These techniques yielded a consistent tempo free period TFR for Nepal. These were found to be suitable for adjusting period fertility, especially when fertility is subject to fluctuating tempo effects. It was also found that the tempo effect amounted to be 0.4 births per women in 1991 whereas it was 0.3 birth per women in 1994. Women are likely to delay their childbearing, which implies that observed fertility is lower than it would have been without tempo changes. The period fertility was declining somewhat slow pace, and declined from as about 5 births in 1989 to as about 4 births in 1995. Nepal Journal of Science and Technology Vol. 7, 2006